A comparative study of the insecticidal potential of clitoria ternatea (butterflypea), desmodium gangeticum (shalparni) and delonix regia (flame tree) methanolic leaf extracts against cimex hemipterus (bed bug) - Advincula, Jhenry C., Baril, Allyssa Maria A., Cruz, Kylle, Garcia, Anaidrene S., Ulep, Judycarla Maria V. 4 0 16; 5
ABSTRACT: Bed bugs, specifically Cimex hemipterus, have been infesting households since thousands of years ago and have caused disturbances, even in health, causing an extensive use of pesticides. This concern led to the study of plants and their phytochemicals containing insecticidal properties as an alternative for bed bug control. Hence, this study focused on the comparison of the insecticidal potential of Clitoria ternatea (Butterfly pea), Desmodium gangeticum (Shalpami), and Delonix regia (Flame tree) against C. hemipterus. Fresh leaves were collected, powdered, and macerated using 82% methanol. Crude extracts were tested for their phytochemicals, specifically flavonoids, terpenoids, alkaloids, steroids, phenols, glycosides, tannins, and saponins. A total of 300 bed bugs were collected, fed, and acclimated for seven days. Thin film method was used for the assay, and triplicates were made for each treatment. Each Petri dish with the treatment was calculated by its percent mortality and was subjected to one-way ANOVA and t-test for independent samples. This resulted in C. hemipterus being greatly affected by the three treatment groups, with a percent mortality ranging from 76% to 92%, indicating no statistical difference between the three groups. No statistical difference was also observed when the extracts were compared to C. citratus (positive control). Thus, the findings demonstrated that all three plants possess nearly identical insecticidal potential against C. hemipterus. Overall, this study provided new insights that would aid in the formulation of new treatments and the improvement of control measures against this pest.
Undergraduate Thesis: (Bachelor of Science in Biology) - Pamantasan ng Lungsod ng Maynila, 2023
Keywords: 2 -- 0; 6; 20; 20; 2